DAMPAK PERKEMBANGAN BISNIS TRANSPORTASI UDARA DALAM RANGKA ASEAN OPEN SKY TERHADAP EKONOMI POLITIK INDONESIA TAHUN 2015-2017 - Erido B Surbakti; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The ASEAN member states have agreed to implement the ASEAN open sky policy in 2015. This policy gives an impact on the aviation world, especially on the freedom to fly across the ASEAN countries. This paper examines the impact  of air transport  business in order  Asean open sky  to  economic growth and politic Indonesia  , Indonesia airline industry conditions, the position of the Indonesian aviation industry compared to other ASEAN countries. The study uses qualitative descriptive approach where secondary data used as the basis of analysis. The study concludes that air transport has a positif  impact on economic growth development and image of aviator Indonesia in global . arising from both supply and demand side. Indonesia itself has a great potential for the development of air transport due its position, which is more profitable than other ASEAN countries. In this regard, government itself should pay attention to the problem of air traffic management and airport infrastructure development in a sustainable manner in order to deal with ASEAN open sky.  Keywords: ASEAN, open sky, aviation, economic growth development